Tracing and Mapping of Cultural Reserves as a Source of Information for Historical Tourism in Langsa City - Bukhari Bukhari; Madhan Anis; Ramazan Ramazan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Cultural heritage objects are evidence of historical heritage that is very useful in life, cultural heritage is also useful as a means of education as well as a historical tourism destination for the community. The purpose of this research is to find out historical heritage buildings in Langsa City, then to map the historical heritage buildings to be used as sources of information.The method in this study uses a historical method with stages namely the heuristic stage, the source criticism stage, the interpretation stage and the historiography stage. The result of the research is that there are five historical heritage buildings in Langsa City that have been designated as a Cultural Heritage with the Letter of the Mayor of Langsa in 2016. Then the mapping is carried out on the historical heritage which has been used as a source of information that is very helpful for local, regional, national and foreign tourists who visit Langsa City.